Seasonal trends of the polyp expansion and nutritional condition of Alcyonium acaule (Octocorallia, Alcyonacea) - Rizzo, Lucia; Fiorillo, Ida; Rossi, Sergio (PeerJ, 2021)
The ecological physiology of anthozoans, as well as their resistance to stressors, are strongly influenced by environmental factors and the availability of resources. The energy budget of anthozoans can vary seasonally in order to find an equilibrium between the available resources and respiration, polyp activity, growth, and reproduction processes. The variation in the biochemical composition of the animal tissues in these organisms results from a combination of the productivity processes of the water column coupled with the reproductive effort and potential starvation periods of the anthozoans. Here, the seasonal variation in the polyp activity of a slow-growing passive suspension feeder, the octocoral Alcyonium acaule, as well as their carbohydrate, protein and lipid contents, was investigated in a warm temperate environment using in-situ observations and biochemical analyses. Polyp activity exhibited a significant variability that was moderately dependent on season, while an aestivation phenomenon in A. acaule (i.e., a resting period in which the anthozoan is not capable of any polyp activity) during the warmer months is clearly observed. Carbohydrate concentrations in the coral species showed a significant increase in the late winter and spring seasons, and the lipid content increased during the spring. A higher abundance of lipids and carbohydrates coincided with a higher primary productivity in the water column, as well as with the octocoral reproduction period. In late autumn, there was a depletion of these biomolecules, with protein levels exhibiting great variability across sampling times. Complex alterations driven by climate change could affect the energy fluxes that depend on the dead or alive particles that are intercepted by marine animal forests. The obtained findings show a food shortage in late summer and autumn of the benthic suspension feeder A. acaule through the integrative descriptors of the ecophysiology of these anthozoans. This research contributes to the knowledge of energy storage capabilities in benthic suspension feeders in general, highlighting the importance of understanding the limits of resistance to starvation periods through these indicators.
Keywords: Marine animal forest; Habitat-forming species; Anthozoans; Polyp expansion; Organic matter; Octocorals; Seasonal changes